Classification of Python Language Modules - Otahanov Nurillo Abdumalikovich (Universitas Muhammadiyah Sidoarjo, 2022)
The Python programming language contains a large number of internal and external modules. In the process of teaching Python or developing a program in that language, it is important to identify the modules available and the areas to which they belong, in other words, to classify the modules into classes. This article deals with the problem of classifying the internal and external modules of the Python programming language. In classifying, the author used a reliable source as well as personal experience and analysis. The article also provides information on the benefits of using DSLs.